ULTRASTRUCTURAL CHANGES OF PINEALOCYTES OF THE PINEAL GLAND UNDER THE ACTION OF METHYLENE BLUE IN RATS OF DIFFERENT AGES - Chumachenko, O.Yu.; Cherno, V.S.; Yablonska, T.M. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the ultrastructural changes of the pineal cells of the pineal gland in normal conditions and under the conditions of long-term exposure to methylene blue. In 14-day-old intact rats, the pineal gland is represented as a formed organ. With age, in 45- and 90-day-old animals, the ultrastructural state of the cytoplasm and nucleus of pinealocytes corresponded to increased activity, but was less pronounced than in 14-day-old animals. Under the effect of methylene blue, in the pineal gland of 14- and 45-day-old rats, structural signs of weakly expressed enhancement of the function of light and dark pinealocytes were noted. In 90-day-old animals, under the effect of methylene blue in the pineal gland, along with the enhancement of the function of light pineal cells, signs of normalization of structure and function were noted in dark ones, which is obviously connected with the inclusion of adaptive mechanisms to the effect of methylene blue. The obtained results open the prospect for further study of the patterns of structural and functional changes of the endocrine glands under the conditions of nitrate intoxication and represent the basis for the development of effective measures for the correction of endocrine system lesions that occur in people as a result of professional activity.
Keywords: gland; endocrine system; intoxication; nitrate poisoning; correction